The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.2478/msp-2022-0025
|View full text |Cite
|
Sign up to set email alerts
|

Development of building materials based on a high content of fly ash and polycondensation products from Chinese heat and power plants

Abstract: The addition of fly ash from thermal power plants (TPP) and chemical additives, such as polycondensation products of acetone and formaldehyde, is an effective and economical method for increasing the strength and durability of building materials, in particular concrete. Fly ash added to the concrete and mortars at 10%–15% does not reduce their technical properties, while polycondensation products of acetone and formaldehyde plasticize and accelerate the hardening process of concrete. The study aims to substant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Earlier, it was because mainly acidic fly ash was used as a hydraulic admixture in heavy concrete [4]. However, work in recent years has shown that basic fly ash can also be used in concrete mixtures [5]. Because the transferred fly ash samples belong to basic fly ash, it is necessary to determine their participation in the Portland cement curing process [16].…”
Section: Analysis Of Previous Researchmentioning
confidence: 99%
“…Earlier, it was because mainly acidic fly ash was used as a hydraulic admixture in heavy concrete [4]. However, work in recent years has shown that basic fly ash can also be used in concrete mixtures [5]. Because the transferred fly ash samples belong to basic fly ash, it is necessary to determine their participation in the Portland cement curing process [16].…”
Section: Analysis Of Previous Researchmentioning
confidence: 99%